Effect of Cucumber (Cucumis sativus) Extract Cream on Aquaporin-3 and Hyaluronic Acid Levels in Wistar Rats with Xerosis Cutis - Ajeng Destian Suparwi; Pasid Harlisa; Siti Thomas Zulaikhah (Althea Medical Journal, 2026)
Background: Xerosis cutis is characterized by impaired barrier function and reduced hydration markers, including Aquaporin-3 (AQP3) and hyaluronic acid (HA).  Cucumber extract (Cucumis sativus) contains antioxidants and humectants compounds that may improve skin hydration. This study investigated the effects of cucumber extract cream on AQP3 and HA levels in female Wistar rats (Rattus norvegicus) with grade II xerosis cutis.Methods:  This in vivo experimental study used a post-test-only control group design. Twenty-five female Wistar rats were randomly assigned into five groups: healthy control, xerosis control, positive control (10% ceramide), and treatment groups receiving 3% and 5% cucumber extract cream. Xerosis was induced by topical application of 70% acetone followed by 100% ethanol for 5–7 days until grade II xerosis developed.  The creams were then applied topically for 14 days. AQP3 and HA levels were measured using enzyme-linked immunosorbent assay (ELISA).Results: HA levels differed significantly among groups (p=0.016). The 5% cucumber extract cream maintained HA levels comparable to healthy controls (611.25±248.61 vs. 685.26±194.95 ng/L; p=0.394). In contrast, ceramide and 3% cucumber treatments showed lower HA levels relative to healthy controls. AQP3 levels showed no statistically significant differences among groups (p=0.131), although descriptively higher expression was observed in the 5% cucumber-treated group.Conclusion: Cucumber extract cream at 5% concentration helps maintain HA levels and shows a tendency to increase AQP3 expression, suggesting potential benefits for improving skin hydration in xerosis cutis and supporting skin health associated with aging.